Peculiarities of the Color Epithets Functioning in the Yakut Heroic Epic Olonkho Text - Koryakina, Raisa Vasilievna (Journal of History Culture and Art Research, 2018)
This article devoted to the semantics of color epithets in the text of the Yakut heroic epic olonkho analysis, as well as to the peculiarities of their functioning in the epic text. An epithet, as an artistic and visual mean, has been attracting the interest of linguists since ancient times. Theoretical and methodological basis of the research consists of the works of A.N. Veselovsky, A.A. Potebnya, V.M. Zhirmunsky, V.Ya. Propp, S.Y. Neklyudov, S.L. Neveleva, as well as of the works of the Yakut scientists I.V. Pukhov, G.U. Ergis, P.A. Sleptsov, N.I. Filippova, V.V. Illarionov and other epics of the Russian Federation peoples researchers. The study of color epithets semantics and their functioning in the text of the Yakut heroic epic olonkho has the purpose of expanding linguistic knowledge about national-cultural specifics of the Yakuts, saved in the epic of olonkho. The relevance of this work lies in the fact that the subject of research – color epithets – is a significant part of the epithet layer in the olonkho text, thus, study of them contributes to a systematic analysis of the vocabulary of the Yakut heroic epic olonkho as a whole. Color epithets are a set of color adjectives “үрүҥ/ маҥ(ҕ)ан” white, “хара” black, “кыhыл” red, “аалай” scarlet, “араҕас” yellow, “бороҥ” gray, “күөх” green/light blue/blue. The object of the research is based on the texts of academic editions of “Nyurgun Bootur the Swift” olonkho by K.G. Orosin, “Kyys Debiliye” olonkho by N.P. Burnashev, “Mighty Er Sogotokh” by V.O. Karataev and “Obstinate Kulun Kullustur” by I.G. Timofeev-Teploukhov. At the initial stage, in the paper used the methods of computer analysis for the selection of color epithets from the olonkho text array, further, to characterize the color epithets and the determined words – methods of dictionary definitions analysis, as well as methods of quantitative, descriptive, contextual and comparative analysis. As shown by the study, color epithets are used in the text of the Yakut olonkho in the description of literally all elements of the epic narrative: time, place, appearance, clothing of heroes, weapons of heroes, their emotions and magical properties. It is established that the informativeness of color epithets, inherent into the semantics of the word and revealed in the combinations of color epithets with determined words, is very large – they express the worldview of the Yakuts, their attitude to the world, their assessment of the environment.